Local anesthetics transfer across the membrane - Kavčič, Hana (Acta chimica slovenica, 2021)
Local anesthetics are one of the most widely used drug classes in clinical practice. Like many other biological molecules, their properties are altered depending on their protonation status, which is dependent on the pH of the environment. We studied the transport energetics of seven local anesthetics from the extracellular fluid across the biological membrane to the axoplasm in order to understand the effect of pH value on their efficacy and other pharmaco-dynamic properties. In this we applied three different methods of solvent reaction field in conjunction with quantum chemical calculations to reproduce experimental values of n-octanol/water partition coefficients for both neutral and protonated forms. Only the SMD method of Cramer and Truhlar was able to reproduce experimental partition coefficient values. The results are discussed in terms of the function of local anesthetics under physiological conditions and in the case of local acidosis.
Keywords: distribution coefficient; local anesthetics; lokalni anestetiki; metode reakcijskega polja s topilom; porazdelitveni koeficient; solvent reaction field methods